Monitoring the high energy universe - Nöthe, Maximilian (Technische Universität Dortmund, 2020)
High energy gamma-ray astronomy probes the most extreme phenomena in our universe: super novae and their remnants as well as supermassive black holes at the center of far away galaxies. The First G-APD Cherenkov Telescope (FACT) is a small, prototype Imaging Air Cherenkov Telescope (IACT) operating since 2011 at the Roque de los Muchachos, La Palma, Spain. It specializes in continuously monitoring the brightest known sources of gamma rays. In this thesis, I present a new, open analysis chain for the data recorded by FACT, with a major focus on ensuring reproducibility and relying on modern, well-tested tools with widespread adoption. The integral sensitivity of FACT was improved by 45 % compared to previous analyses by the introduction of an improved algorithm for the reconstruction of origin of the gamma rays and many smaller improvements in the preprocessing. Sensitivity is evaluated both on simulated datasets as well as observations of the Crab Nebula, the “standard candle” of gamma-ray astronomy. Another major advantage of this new analysis chain is the elimination of the dependence on a known point source position from the event reconstruction, thus enabling the creation of skymaps, the analysis of observations where the source position is not exactly known and sharing reconstructed events in the now standardized format for open gamma-ray astronomy. This has lead to the first publication of a joined, multi-instrument analysis on open data of four currently operating Cherenkov telescopes. A smaller second part of this thesis is concerned with enabling robotic operation of FACT, which is now the first Cherenkov telescope, where no operators are required during regular observations.

Die Hochenergie-Gammaastronomie erlaubt es, die extremsten Phänomene in unserem Universum zu untersuchen: Supernovae und ihre Überreste sowie supermassive schwarze Löcher in den Zentren weit entfernter Galaxien. Das First G-APD Cherenkov Telescope (FACT) ist ein kleines, bildgebendes, atmosphärisches Tscherenkow Teleskop, dass seit Oktober 2011 auf dem Roque de los Muchachos, La Palma, Spanien beobachtet. Es ist auf die Langzeitbeobachtung der hellsten bekannten Gammastrahlungsquellen spezialisiert. In dieser Arbeit stelle ich eine neue, öffentliche Analysekette für die von FACT aufgenommen Daten vor. Ein Hauptaugenmerk wurde auf die Reproduzierbarkeit und die Verwendung moderner, gut getesteter und weit verbreiteter Methoden gelegt. Die integrale Sensitivität von FACT wurde im Vergleich zu früheren Analysen um 45 % gesteigert, hauptsächlich durch die Einführung einer verbesserten Methode zur Bestimmung der Herkunft der Gammastrahlung, sowie durch viele weitere, kleinere Verbesserungen in der Vorverarbeitung. Die Sensitivität wurde sowohl auf simulierten Daten als auch auf Beobachtungen des Krebsnebels, der Standardkerze der Gammaastronomie, ausgewertet. Ein weiterer Vorteil der neuentwickelten Analysekette ist ihre Unabhängigkeit von Annahmen über eine bekannte Punktquelle. Dies ermöglicht die Erstellung von Himmelskarten, die Analyse von Beobachtungen, bei denen die Quellposition nicht genau bekannt ist und das Speichern und Veröffentlichen rekonstruierter Ereignisse im nun standardisiertem Datenformat für offene Gammaastronomie. Die hat die Publikation der ersten gemeinsamen Analyse von Krebsnebel-Daten von vier aktuell beobachtenden Tscherenkow-Teleskopen ermöglicht. Der zweite, kleinere Teil dieser Arbeit beschäftigt sich mit der Robotisierung von FACT, welches nun das erste Tscherenkow-Teleskop ist, für dessen reguläre Observationen kein Personal mehr benötigt wird.
Open, reproducible, machine learning based analysis for the First G-APD Cherenkov Telescope
Keywords: Gamma-ray astronomy; FACT; Machine learning; Astroparticle physics; Cherenkov astronomy; Aict-tools; Disp method; Sensitivity; IACT; 530; Gammaastronomie; Cherenkov Telescope Array; Astrophysik; Maschinelles Lernen; Reproduzierbarkeit; Sensitivität